(untitled) (Castilla. Estudios de Literatura, 2015)
This article analyzes The aunt Águeda as a Bildungsroman that dialogues with the speech of confession: the history is told by a female conscience deliberating on a stage of his past: the traffic of the infancy to the youth, duality be configured to be a narrator- to be narrated. For our analysis we rely on reflections Maria Zambrano wrote about the act of confession and the temporality of life and death. The experiences of Eros and Thanatos forged an identity that affirms its “learn from suffering” by means of the novelizada confession.